Multifunctional protein APPL2 contributes to survival of human glioma cells - Pyrzynska, Beata (John Wiley and Sons Inc., 2012)
Some endocytic proteins have recently been shown to play a role in tumorigenesis. In this study, we demonstrate that APPL2, an adapter protein with known endocytic functions, is upregulated in 40% cases of glioblastoma multiforme, the most common and aggressive cancer of the central nervous system. The silencing of APPL2 expression by small interfering RNAs (siRNAs) in glioma cells markedly reduces cell survival under conditions of low growth factor availability and enhances apoptosis (measured by executor caspase activity). Long‐term depletion of APPL2 by short hairpin RNAs (shRNAs), under regular growth factor availability, suppresses the cell transformation abilities, assessed by inhibited colony formation in soft agar and by reduced xenograft tumor growth in vivo. At the molecular level, the negative effect of APPL2 knockdown on cell survival is not due to the alterations in AKT or GSK3β activities which were reported to be modulated by APPL proteins. Instead, we attribute the reduced cell survival upon APPL2 depletion to the changes in gene expression, in particular to the upregulation of apoptosis‐related genes, such as UNC5B (a proapoptotic dependence receptor) and HRK (harakiri, an activator of apoptosis, which antagonizes anti‐apoptotic function of Bcl2). In support of this notion, the loss of glioma cell survival upon APPL2 knockdown can be rescued either by an excess of netrin‐1, the prosurvival ligand of UNC5B or by simultaneous silencing of HRK. Consistently, APPL2 overexpression reduces expression of HRK and caspase activation in cells treated with apoptosis inducers, resulting in the enhancement of cell viability. This prosurvival activity of APPL2 is independent of its endosomal localization. Cumulatively, our data indicate that a high level of APPL2 protein might enhance glioblastoma growth by maintaining low expression level of genes responsible for cell death induction.